Деятельность Ялтинского благотворительного общества в 1903 году (по материалам дома-музея А. П. Чехова в Ялте) - Ничипорук, Н.Г. (Культура народов Причерноморья, 2014)
В статье подробно рассматривается отчет Ялтинского благотворительного общества о
его работе за 1903г. Актуальность заявленной темы обусловлена возрастающей ролью
благотворительных организаций в жизни современного украинского общества и необходимостью
использовать позитивный опыт аналогичных дореволюционных организаций. Целью исследования
является всесторонний анализ деятельности Ялтинского благотворительного общества в 1903г.
Делается вывод о многофункциональности деятельности Ялтинского благотворительного общества. У статті докладно розглядається звіт Ялтинського благодійного товариства про його
роботу за 1903 р. Актуальність заявленої теми обумовлена зростаючою роллю благодійних організацій в
житті сучасного українського суспільства та необхідністю використовувати позитивний досвід
аналогічних дореволюційних організацій. Метою дослідження є всебічний аналіз діяльності Ялтинського
благодійного товариства у 1903 р. Робиться висновок про багатофункціональність діяльності
Ялтинського благодійного товариства. In the article is examined the report Yalta Charitable Society on its work in 1903. The relevance of
the declared theme due to increasing role of charities in contemporary Ukrainian society and the necessity of
using the positive experience of the similar pre-revolutionary organizations. The comprehensive analysis of
activity of the Yalta Charitable Society in 1903 is the purpose of this study. The structure of the Yalta Charitable
Society, which included shelters, guardianships, a dining room, a tea room and other charities, is considered in
the article. The procedure for their functioning, depending on the time of year and the social situation in the city
was determined too. Based on the study of information which contains in the report on the work of the Society in
1903 was ascertained the main sources of financing of its activity. The major of them were private donations
that have been made not only in cash, but in necessary goods and services. In this regard an important role in
the activities of the Society was played by citizens. Many of them were not only its activists, but also made a
significant contribution of their own money to implement the necessary measures. It is concluded about
multifunctionality of activity of Yalta Charitable Society and the possibility of using its experience in solving
critical social problems and building the transparent structure of a charitable organization.